WHO'S AFRAID OF THEOSCIENTOGRAPHY? AN INTERPRETATIVE HYPOTHESIS ON HARUN YAHYA. Issue 1 (March 2014) - Bigliardi, Stefano
Abstract I scrutinize the ideas and works of the Turkish religious leader and author Adnan Oktar/Harun Yahya. I argue for a new definition of Yahya as the representative of what I call theoscientography, proposing to study his work according to such a model rather than in the light of his "Islamic creationism"